Single-layer stable graphene-based film and preparation method thereof

The three-dimensional structure interspersed with metal indium by vapor deposition method was prepared and physically modified, which solved the problem of insufficient stability and conductivity of the single-layer graphene film, and achieved high-performance graphene film preparation.

CN119121177AInactive Publication Date: 2024-12-13DONGGUAN YOUJIN ELECTRONICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411013182.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to prepare a single-layer graphene film with uniform thickness and stable thickness, and graphene nanosheets are prone to stack layer by layer, resulting in insufficient conductivity and stability.

Method used

The three-dimensional structure interspersed metal indium is prepared by vapor deposition method, and combined with the coupling agent for physical modification. Magneto-controlled sputtering bombardment forms indium particles with sharp angles and binds to carbon ion hanging bonds, and performs friction point microplasma treatment. Improve the conductivity and stability of the film.

Benefits of technology

A stable and conductive single-layer graphene film is achieved, which improves the specific surface area and conductivity, avoids the agglomeration of the graphene layer, and enhances the stability and electrical properties of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004964979230000101
    Figure BDA0004964979230000101
  • Figure BDA0004964979230000111
    Figure BDA0004964979230000111
Patent Text Reader

Abstract

The invention discloses a single-layer stable graphene-based thin film and a preparation method thereof, and relates to the technical field of thin films. The preparation method comprises the following steps: preparing a single-layer graphene film by using a chemical vapor deposition method; a three-dimensional porous structure is constructed on the basis of single-layer graphene, metal indium particles and carbon ion dangling bonds are combined through magnetron sputtering bombardment, and the overall conductivity of the film is further improved; a silane coupling agent is used as an auxiliary agent to be chemically linked with the graphene layer, so that the stability of the graphene layer in the resin is improved, and the three-dimensional structure of the graphene layer is not easily agglomerated and damaged; friction point micro-plasma treatment modification is carried out on the whole film, so that generated oxygen ions are attached to the surface of the film, the electrical property of the material is improved, and the conductivity of the material is improved; the state of oxygen ions in the thin film is unstable, and the oxygen ions are partially desorbed in a heating mode, so that the regulation and control of the structural stability of the thin film are realized. The thin film prepared by the method has stable and conductive effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of thin film technology, in particular to a single-layer stable graphene-based thin film and a preparation method thereof. Background Art

[0002] Graphene should be widely used, and its premise is to obtain graphene materials with a strict monolayer thickness, and the methods commonly used at present are mechanical exfoliation, epitaxial growth, chemical vapor deposition and graphite oxide reduction. Mechanical exfoliation can obtain high-quality graphene samples, but its operation steps are cumbersome, inefficient and low in yield. The oxidant used in the graphite oxide reduction method has a destructive effect on the graphite layer, and the resulting graphene is of poor quality and has more defects. The above various methods also have a defect, that is, graphene materials with uniform thickness and monoatomic layer thickness cannot be obtained. And the preparation of thin films with monolayer graphene cannot meet the demand for film stability, and it is necessary to carry out appropriate modification and preparation process optimization of the monolayer graphene base.

[0003] The strong van der Waals forces between graphene nanosheets and the hydrophobic properties of graphene make it very easy for graphene sheets to stack layer by layer. How to synthesize high-performance single-layer graphene films is a key issue in the research of graphene-based films. Constructing a graphene-based porous three-dimensional framework structure and interspersing metal ions is a very effective method. Compared with original graphene and other graphene-based materials with morphological structures, graphene-based materials with three-dimensional framework structures show more excellent physical and chemical properties based on their three-dimensional network and porous structural characteristics. Three-dimensional graphene materials are different from two-dimensional graphene in structure. They effectively overcome the shortcomings of two-dimensional graphene, which is easy to agglomerate, difficult to disperse, and difficult to obtain a high specific surface area. Summary of the invention

[0004] The object of the present invention is to provide a single-layer stable graphene-based film and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a single-layer stable graphene-based film, wherein the film is a three-dimensional structure prepared by vapor-depositing a single-layer graphene interspersed with metal indium, which is physically modified by combining with a coupling agent.

[0006] Furthermore, the three-dimensional structure is interspersed with metal indium ions by magnetron sputtering bombardment, so that the indium particles are crushed by impact to form particles with sharp angles, thereby combining with the three-dimensional graphene carbon ion dangling bonds.

[0007] Furthermore, the physical modification is to perform friction point micro plasma treatment modification on the film, so that the generated oxygen ions are attached to the surface of the film, and then partially desorbed by increasing the temperature.

[0008] Furthermore, a method for preparing a single-layer stable graphene-based film comprises the following preparation steps:

[0009] (1) The copper foil was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water at a power of 30kHz for 10 minutes respectively; the cleaned copper foil was placed in a quartz boat and placed in a stable temperature zone in the furnace tube, and the tube mouth was closed; the vacuum pump was turned on to evacuate the air in the system, and when the vacuum degree reached -0.1MPa, the outlet valve was closed, and H2 was introduced until the system was at normal pressure. At this time, H2 was turned off, and the outlet valve was opened to continue vacuuming, and this was repeated twice; the heating function of the tubular furnace was turned on to anneal the copper foil; after the annealing was completed, the H2 flow rate was maintained, the temperature was adjusted to 1000-1060°C, CH4 was introduced, the flow rate was controlled at 10-50sccm, the reaction time was 10-50min, and CH4 was turned off after the reaction was completed; the heating function of the tubular furnace was turned off, and the temperature was lowered while keeping the H2 flow rate unchanged; after it dropped to room temperature, H2 was turned off, the vent valve was opened until the system was at normal pressure, and the sample was taken out to obtain a single-layer graphene;

[0010] (2) Prepare 12-16 parts of 5-15% ethyl cellulose ethanol solution, stir at 60 rpm for 20 min, then add 9.8 parts of terpineol and 9.2 parts of anhydrous ethanol; finally add 0.1-0.2 parts of the prepared ground single-layer graphene powder, stir magnetically at 150-250 rpm for 20-30 min, then ultrasonically disperse at 40 kHz for 20 min, alternating 3-5 times; then stir and evaporate at 50° C. and 600-1000 rpm until no more weight loss occurs, then add 0.5-0.7 parts of acetylacetone and 0.6-0.8 parts of OP emulsifier are added, and graphene slurry is obtained after stirring at 100 rpm for 30 minutes; 3-5 layers of graphene slurry are screen-printed on the cleaned FTO glass conductive surface, and pre-treated in a forced air drying oven at 80-120° C. for 20 minutes, and then the printing is repeated, and the surface is cured at 100-150° C. for 2-4 hours, and then 3-5 layers of graphene slurry are printed, and finally the surface is heat-treated at 100-400° C. for 1 hour in a muffle furnace, and then cooled to room temperature to obtain three-dimensional graphene;

[0011] (3) turning on the hydrogen source in the magnetron sputtering vacuum chamber, and sputtering hydrogen with a radio frequency power of 100-150W to generate hydrogen plasma, and bombarding the three-dimensional graphene with the hydrogen plasma; using single crystal SiC as a substrate, laying the bombarded three-dimensional graphene on the substrate, heating to 450-550°C, opening the baffle of the metal beam source to deposit metal indium atoms; then turning on the nitrogen source in the magnetron sputtering vacuum chamber, sputtering nitrogen with a radio frequency power of 100-150W to generate nitrogen plasma, and bombarding the deposited composite with the nitrogen plasma; then annealing at 500-750°C, maintaining for 15-30min to obtain metal indium interspersed with the three-dimensional graphene;

[0012] (4) adding 10 parts of metal indium interpenetrating three-dimensional graphene and 10-14 parts of silane coupling agent to 50 parts of dry dimethylformamide, stirring at 60 rpm for 30 minutes, reacting at 20-50° C. for 12-24 hours, cooling to room temperature and filtering, washing with dimethylformamide twice, and drying at 50° C. to constant weight to obtain surface-modified graphene; adding 5-50 parts of surface-modified graphene to 50-100 parts of dimethylformamide and ultrasonically dispersing them uniformly, and then adding 100 parts of terephthalic acid and 35-45 parts of ethylene dichloride; alcohol, 1-2 parts of catalyst and 1-2 parts of stabilizer, stirring at 60-180rpm for 20-60min, then reducing the pressure to 102Pa, and heating to 250-280℃ for polycondensation for 30-180min, and discharging the material to obtain polyester PET chips; drying the polyester chips at 160-180℃ for 2-4h, extruding them at 265-295℃ through an extruder, and then cooling them at 12-20℃ to make casting sheets; and biaxially stretching to obtain a graphene-based film with a thickness of 3-20μm;

[0013] (5) The film was modified by triboelectric microplasma. The friction nanogenerator used copper film as the positive electrode material and polytetrafluoroethylene as the negative electrode material. The copper foil and polytetrafluoroethylene were cut into squares of 10 cm × 10 cm respectively and then pasted on acrylic plates of the same size as two fixed electrodes. The movement of the friction nanogenerator was controlled by a linear motor. The high voltage output by the friction nanogenerator acted on the needle tip above the film, and the discharge current was controlled to be between 4.5 and 6.5 μA. The distance between the needle tip and the film was 0 to 1 mm, and the time was 0 to 14 s. After being treated at 160 to 200 °C for 5 to 15 min, a stable graphene-based film was obtained.

[0014] Furthermore, the annealing process conditions in step (1) are as follows: temperature is 1050° C., time is 20 min, hydrogen flow rate is 10 sccm, and the vacuum gauge shows a pressure of approximately -0.1 MPa.

[0015] Furthermore, the single-layer graphene grinding process in step (2) is as follows: the mass ratio of cobalt oxide ball milling beads to single-layer graphene is 2000-10000:1, the rotation speed is 200-400rpm, and the ball milling time is 10-30h.

[0016] Furthermore, in the step (3), the deposition process conditions are as follows: a heating current of 2.0-3.0 A, a heating temperature of 950-1020 K, and a heating time of 15-25 min.

[0017] Furthermore, in step (4), the silane coupling agent is one of γ-glycidyloxypropyltrimethoxysilane and silane coupling agent KH550.

[0018] Furthermore, in step (4), the catalyst is antimony trioxide.

[0019] Furthermore, in step (4), the stabilizer is triphenyl phosphate.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] The invention prepares a three-dimensional structure by vapor-depositing a single-layer graphene, interspersing metal indium, and combining it with a coupling agent to prepare a film, which is then physically modified to achieve a stable and conductive effect.

[0022] First, a single-layer graphene film is prepared by vapor phase chemical deposition. As the preparation reaction time increases, the cracked carbon atoms continue to grow into a film on the surface of the copper foil with the active core as the center, and the size of the single crystal increases accordingly. The grains are basically oriented parallel to each other to achieve a uniform single-layer structure. The graphene monomer film formed by the honeycomb-shaped two-dimensional crystal composed of a single layer of hexagonal carbon atoms will have a large number of dangling bonds of carbon atoms around it, and other carbon atoms that do not participate in nucleation are connected to it, resulting in an unstable single-layer graphene structure. A three-dimensional porous structure is constructed based on the single-layer graphene. This multi-dimensional structure effectively increases the specific surface area of ​​graphene and provides favorable conditions for the subsequent doping of metal particles. Nano-scale indium particles are interspersed in it, and through magnetron sputtering bombardment, the indium particles are formed into particles with sharp angles under impact crushing, thereby combining with the hydroxyl functional groups, carboxyl functional groups, and carbonyl functional groups generated by the dangling bonds of carbon ions, while solving the instability caused by the dangling bonds, further improving the overall conductivity of the film. The interaction between the prepared graphene and the substrate is weak, and the graphene is in a separated state, which achieves the effect of ionization. It is not easy to agglomerate in the subsequent preparation process and is stably and evenly dispersed in the resin.

[0023] Secondly, silane coupling agent is used as an auxiliary agent to chemically link with the graphene layer, which not only improves its stability in the resin, but also makes it less likely to agglomerate and destroy its three-dimensional structure after surface modification; the graphene layer in the resin is modified by friction point microplasma treatment as a whole, so that the generated oxygen ions adhere to the surface of the film, improving the electrical properties of the material and increasing its conductivity; at the same time, the state of oxygen ions in the film is not stable, and they can be partially desorbed by heating, thereby achieving the regulation of the stability of the film structure, so that the film can improve the electrical properties while taking into account stability. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the index testing methods of a single-layer stable graphene-based film and its preparation method prepared in the following examples as follows:

[0026] Thermal stability: Take 5 samples of the film of the embodiment and the comparative example, draw perpendicular 100mm*100mm marking lines in the middle of the vertical and horizontal directions of the samples, place them flat in a constant temperature oven at (150±1)℃, keep them for 30 minutes, then take them out, cool them to ambient temperature, measure the length of the longitudinal marking line, calculate the thermal shrinkage of the samples, and take the arithmetic mean.

[0027] Conductivity: The conductivity of the films prepared in the examples and comparative examples was measured before and after being immersed in a dilute sulfuric acid solution. The surface resistance of the films was measured using a four-probe tester, and the conductivity of the films was calculated based on the relationship between the surface resistance and the thickness of the films.

[0028] Example 1

[0029] (1) The copper foil was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water at a power of 30kHz for 10 minutes respectively; the cleaned copper foil was placed in a quartz boat in a stable temperature zone in a furnace tube and the tube mouth was closed; the vacuum pump was turned on to extract the air in the system. When the vacuum degree reached -0.1MPa, the outlet valve was closed and H2 was introduced into the system until the system was at normal pressure. At this time, H2 was turned off and the outlet valve was opened to continue vacuuming. This was repeated twice; the heating function of the tubular furnace was turned on to anneal the copper foil. The temperature is 1050°C, the time is 20 minutes, the hydrogen flow rate is 10 sccm, and the vacuum gauge shows a pressure of about -0.1 MPa; after annealing, the H2 flow rate is maintained, the temperature is adjusted to 1000°C, CH4 is introduced, the flow rate is controlled at 10 sccm, the reaction time is 10 minutes, and after the reaction is completed, CH4 is turned off; the heating function of the tubular furnace is turned off, and the temperature is lowered while the H2 flow rate is maintained unchanged; after it drops to room temperature, H2 is turned off, the vent valve is opened until the system is at normal pressure, and the sample is taken out to obtain a single-layer graphene;

[0030] (2) The mass ratio of cobalt oxide ball milling beads to single-layer graphene was 2000:1, the rotation speed was 200 rpm, and the ball milling time was 10 h to obtain the ground single-layer graphene powder; 12 parts of 5% ethyl cellulose ethanol solution was prepared, stirred at 60 rpm for 20 min, and then 9.8 parts of pine alcohol and 9.2 parts of anhydrous ethanol were added; finally, 0.1 parts of the prepared single-layer graphene powder was added, magnetic stirring was performed at 150 rpm for 20 min, and then ultrasonic dispersion was performed at 40 kHz for 20 min, and then the mixture was stirred for 20 min. The mixture was stirred for 3 times at 50°C and 600 rpm for evaporation until no more weight loss was observed, and then 0.5 parts of acetylacetone and 0.6 parts of OP emulsifier were added, and the mixture was stirred at 100 rpm for 30 min to obtain graphene slurry. Three layers of graphene slurry were screen-printed on the cleaned FTO glass conductive surface, and the surface was pretreated at 80°C in a forced air drying oven for 20 min, and then the printing was repeated, and the mixture was cured at 100°C for 2 h, and then three layers of graphene slurry were printed, and finally the surface was heat-treated at 100°C for 1 h in a muffle furnace, and then cooled to room temperature to obtain three-dimensional graphene.

[0031] (3) Turn on the hydrogen source in the magnetron sputtering vacuum chamber, and sputter hydrogen with a radio frequency power of 100 W to generate hydrogen plasma, and use the hydrogen plasma to bombard the three-dimensional graphene; use single crystal SiC as a substrate, lay the bombarded three-dimensional graphene on the substrate, heat it to 450°C, open the baffle of the metal beam source to deposit metal indium atoms, the heating current is 2.0A, the heating temperature is 950K, and the heating time is 15min; then turn on the nitrogen source in the magnetron sputtering vacuum chamber, sputter nitrogen with a radio frequency power of 100W to generate nitrogen plasma, and use the nitrogen plasma to bombard the deposited composite; then anneal at 500°C and keep it for 15min to obtain metal indium interspersed with three-dimensional graphene;

[0032] (4) Add 10 parts of metal indium intercalated three-dimensional graphene and 10 parts of γ-glycidyloxypropyl trimethoxysilane silane coupling agent to 50 parts of dry dimethylformamide, stir at 60 rpm for 30 minutes, react at 20°C for 12 hours, cool to room temperature and filter, wash twice with dimethylformamide, and dry at 50°C to constant weight to obtain surface-modified graphene; add 5 parts of surface-modified graphene to 50 parts of dimethylformamide and disperse evenly by ultrasonication, and then add 100 parts of Terephthalic acid, 35 parts of ethylene glycol, 1 part of antimony trioxide catalyst and 1 part of triphenyl phosphate stabilizer were stirred at 60 rpm for 20 minutes, then the pressure was reduced to 102 Pa, and the temperature was raised to 250°C for polycondensation for 30 minutes, and the polyester PET chips were obtained; the polyester chips were dried at 160°C for 2 hours, extruded at 265°C by an extruder, and then cold-drummed at 12°C to form a cast sheet; a graphene-based film with a thickness of 3 μm was obtained by biaxial stretching;

[0033] (5) The film was modified by triboelectric microplasma. The friction nanogenerator used copper film as the positive electrode material and polytetrafluoroethylene as the negative electrode material. The copper foil and polytetrafluoroethylene were cut into squares of 10 cm × 10 cm respectively and then pasted on acrylic plates of the same size as two fixed electrodes. The movement of the friction nanogenerator was controlled by a linear motor. The high voltage output by the friction nanogenerator acted on the needle tip above the film, and the discharge current was controlled to be between 4.5 μA, the distance between the needle tip and the film was 0 mm, the time was 0 s, and then treated at 160 ° C for 5 min to obtain a stable graphene-based film.

[0034] Example 2

[0035] (1) The copper foil was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water at a power of 30kHz for 10 minutes respectively; the cleaned copper foil was placed in a quartz boat in a stable temperature zone in a furnace tube and the tube mouth was closed; the vacuum pump was turned on to extract the air in the system. When the vacuum degree reached -0.1MPa, the outlet valve was closed and H2 was introduced into the system until the system was at normal pressure. At this time, H2 was turned off and the outlet valve was opened to continue vacuuming. This was repeated twice; the heating function of the tubular furnace was turned on to anneal the copper foil. The temperature is 1050°C, the time is 20 minutes, the hydrogen flow rate is 10 sccm, and the vacuum gauge shows a pressure of about -0.1 MPa; after annealing, the H2 flow rate is maintained, the temperature is adjusted to 1030°C, CH4 is introduced, the flow rate is controlled at 30 sccm, the reaction time is 30 minutes, and after the reaction is completed, CH4 is turned off; the heating function of the tubular furnace is turned off, and the temperature is lowered while the H2 flow rate is maintained unchanged; after it drops to room temperature, H2 is turned off, the vent valve is opened until the system is at normal pressure, and the sample is taken out to obtain a single-layer graphene;

[0036] (2) The mass ratio of cobalt oxide ball milling beads to single-layer graphene is 6000:1, the rotation speed is 300 rpm, and the ball milling time is 20 hours to obtain the ground single-layer graphene powder; 14 parts of ethyl cellulose ethanol solution with a mass fraction of 10% is prepared, and after stirring at 60 rpm for 20 minutes, 9.8 parts of pine alcohol and 9.2 parts of anhydrous ethanol are added; finally, 0.15 parts of the prepared single-layer graphene powder is added, and magnetic stirring is performed at 200 rpm for 25 minutes, and then ultrasonic dispersion is performed at 40 kHz for 20 minutes. 4 times; then, evaporating with stirring at 50°C and 800rpm until no more weight loss, adding 0.6 parts of acetylacetone and 0.7 parts of OP emulsifier, stirring at 100rpm for 30min to obtain graphene slurry; screen printing 4 layers of graphene slurry on the cleaned FTO glass conductive surface, placing it in a blast drying oven for pretreatment at 100°C for 20min, then repeating the printing, curing at 125°C for 3h, and then printing 4 layers of graphene slurry, and finally heat treating at 250°C in a muffle furnace for 1h, and cooling to room temperature to obtain three-dimensional graphene;

[0037] (3) Turn on the hydrogen source in the magnetron sputtering vacuum chamber, and sputter hydrogen with a radio frequency power of 125 W to generate hydrogen plasma, and use the hydrogen plasma to bombard the three-dimensional graphene; use single crystal SiC as a substrate, lay the bombarded three-dimensional graphene on the substrate, heat it to 500°C, open the baffle of the metal beam source to deposit metal indium atoms, the heating current is 2.5A, the heating temperature is 985K, and the heating time is 20min; then turn on the nitrogen source in the magnetron sputtering vacuum chamber, sputter nitrogen with a radio frequency power of 125W to generate nitrogen plasma, and use the nitrogen plasma to bombard the deposited composite; then anneal at 625°C and keep it for 27.5min to obtain metal indium interspersed with three-dimensional graphene;

[0038] (4) Add 10 parts of metal indium intercalated three-dimensional graphene and 12 parts of γ-glycidyloxypropyl trimethoxysilane silane coupling agent to 50 parts of dry dimethylformamide, stir at 60 rpm for 30 minutes, react at 35°C for 18 hours, cool to room temperature and filter, wash twice with dimethylformamide, and dry at 50°C to constant weight to obtain surface-modified graphene; add 25 parts of surface-modified graphene to 75 parts of dimethylformamide and disperse evenly by ultrasonication, and then add 100 parts of terephthalate. Formic acid, 40 parts of ethylene glycol, 1.5 parts of antimony trioxide catalyst and 1.5 parts of triphenyl phosphate stabilizer were stirred at 120 rpm for 40 min, then the pressure was reduced to 102 Pa, and the temperature was raised to 265°C for polycondensation for 105 min, and polyester PET chips were obtained; the polyester chips were dried at 170°C for 3 h, extruded at 280°C by an extruder, and then cold-drummed at 16°C to form a cast sheet; a graphene-based film with a thickness of 12 μm was obtained by biaxial stretching;

[0039] (5) The film was modified by triboelectric microplasma. The friction nanogenerator used copper film as the positive electrode material and polytetrafluoroethylene as the negative electrode material. The copper foil and polytetrafluoroethylene were cut into squares of 10 cm × 10 cm respectively and then pasted on acrylic plates of the same size as two fixed electrodes. The movement of the friction nanogenerator was controlled by a linear motor. The high voltage output by the friction nanogenerator acted on the needle tip above the film, and the discharge current was controlled to be between 5.5 μA. The distance between the needle tip and the film was 0.5 mm, and the time was 7 s. After being treated at 180°C for 10 min, a stable graphene-based film was obtained.

[0040] Example 3

[0041] (1) The copper foil was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water at a power of 30kHz for 10 minutes respectively; the cleaned copper foil was placed in a quartz boat in a stable temperature zone in a furnace tube and the tube mouth was closed; the vacuum pump was turned on to extract the air in the system. When the vacuum degree reached -0.1MPa, the outlet valve was closed and H2 was introduced into the system until the system was at normal pressure. At this time, H2 was turned off and the outlet valve was opened to continue vacuuming. This was repeated twice; the heating function of the tubular furnace was turned on to anneal the copper foil. The temperature is 1050°C, the time is 20 minutes, the hydrogen flow rate is 10 sccm, and the vacuum gauge shows a pressure of about -0.1 MPa; after annealing, the H2 flow rate is maintained, the temperature is adjusted to 1060°C, CH4 is introduced, the flow rate is controlled at 50 sccm, the reaction time is 50 minutes, and after the reaction is completed, CH4 is turned off; the heating function of the tubular furnace is turned off, and the temperature is lowered while the H2 flow rate is maintained unchanged; after it drops to room temperature, H2 is turned off, the vent valve is opened until the system is at normal pressure, and the sample is taken out to obtain a single-layer graphene;

[0042] (2) The mass ratio of cobalt oxide ball milling beads to single-layer graphene is 10000:1, the rotation speed is 400 rpm, and the ball milling time is 30 hours to obtain the ground single-layer graphene powder; 16 parts of ethyl cellulose ethanol solution with a mass fraction of 15% is prepared, and after stirring at 60 rpm for 20 minutes, 9.8 parts of pine alcohol and 9.2 parts of anhydrous ethanol are added; finally, 0.2 parts of the prepared single-layer graphene powder is added, and magnetic stirring is performed at 250 rpm for 30 minutes, and then ultrasonic dispersion is performed at 40 kHz for 20 minutes, and cross-linking is performed. 5 times; then stir and evaporate at 50°C and 1000rpm until no more weight loss, then add 0.7 parts of acetylacetone and 0.8 parts of OP emulsifier, stir at 100rpm for 30min to obtain graphene slurry; screen print 5 layers of graphene slurry on the cleaned FTO glass conductive surface, place in a blast drying oven at 120°C for pretreatment for 20min, then repeat printing, cure at 150°C for 4h, then print 5 layers of graphene slurry, finally heat treat at 400°C in a muffle furnace for 1h, and cool to room temperature to obtain three-dimensional graphene;

[0043] (3) Turn on the hydrogen source in the magnetron sputtering vacuum chamber, and sputter hydrogen with a radio frequency power of 150W to generate hydrogen plasma, and use the hydrogen plasma to bombard the three-dimensional graphene; use single crystal SiC as a substrate, lay the bombarded three-dimensional graphene on the substrate, heat it to 550°C, open the baffle of the metal beam source to deposit metal indium atoms, the heating current is 3.0A, the heating temperature is 1020K, and the heating time is 25min; then turn on the nitrogen source in the magnetron sputtering vacuum chamber, sputter nitrogen with a radio frequency power of 150W to generate nitrogen plasma, and use the nitrogen plasma to bombard the deposited composite; then anneal at 750°C and keep it for 30min to obtain metal indium interspersed with three-dimensional graphene;

[0044] (4) Add 10 parts of metal indium intercalated three-dimensional graphene and 14 parts of silane coupling agent KH550 to 50 parts of dry dimethylformamide, stir at 60 rpm for 30 minutes, react at 50°C for 24 hours, cool to room temperature and filter, wash twice with dimethylformamide, and dry at 50°C to constant weight to obtain surface-modified graphene; add 50 parts of surface-modified graphene to 100 parts of dimethylformamide and disperse evenly by ultrasonication, then add 100 parts of terephthalic acid, 45 parts of ethylene glycol, 2 parts of catalyst antimony trioxide and 2 parts of stabilizer triphenyl phosphate were stirred at 180 rpm for 60 min, then the pressure was reduced to 102 Pa, and the temperature was raised to 280°C for polycondensation for 180 min, and the polyester PET chips were obtained; the polyester chips were dried at 180°C for 4 h, extruded at 295°C by an extruder, and then cold-drummed at 20°C to form a cast sheet; a graphene-based film with a thickness of 20 μm was obtained by biaxial stretching;

[0045] (5) The film was modified by triboelectric microplasma. The friction nanogenerator used copper film as the positive electrode material and polytetrafluoroethylene as the negative electrode material. The copper foil and polytetrafluoroethylene were cut into squares of 10 cm × 10 cm respectively and then pasted on acrylic plates of the same size as two fixed electrodes. The movement of the friction nanogenerator was controlled by a linear motor. The high voltage output by the friction nanogenerator acted on the needle tip above the film, and the discharge current was controlled to be between 6.5 μA. The distance between the needle tip and the film was 1 mm, and the time was 14 s. After being treated at 200 °C for 15 min, a stable graphene-based film was obtained.

[0046] Comparative Example 1

[0047] The difference between Comparative Example 1 and Example 2 is that there is no step (2), and steps (3) and (4) are changed to: (3) the mass ratio of cobalt oxide ball milling beads to single-layer graphene is 6000:1, the rotation speed is 300 rpm, and the ball milling time is 20 hours to obtain ground single-layer graphene powder; the hydrogen source in the magnetron sputtering vacuum chamber is turned on, and hydrogen is sputtered by 125W radio frequency power to generate hydrogen plasma, and the single-layer graphene is bombarded with hydrogen plasma; single crystal SiC is used as a substrate, and the bombarded single-layer graphene is The single-layer graphene is laid flat on the substrate, and after heating to 500°C, the baffle of the metal beam source is opened to deposit metal indium atoms, with a heating current of 2.5A, a heating temperature of 985K, and a heating time of 20min; then the nitrogen source in the magnetron sputtering vacuum chamber is turned on, and nitrogen is sputtered by 125W of radio frequency power to generate nitrogen plasma, and the deposited composite is bombarded with nitrogen plasma; then annealing is performed at 625°C and maintained for 27.5min to obtain metal indium interspersed with a single-layer graphene;

[0048] (4) Add 10 parts of metal indium intercalated monolayer graphene and 12 parts of γ-glycidyloxypropyl trimethoxysilane silane coupling agent to 50 parts of dry dimethylformamide, stir at 60 rpm for 30 minutes, react at 35°C for 18 hours, cool to room temperature and filter, wash twice with dimethylformamide, and dry at 50°C to constant weight to obtain surface-modified graphene; add 25 parts of surface-modified graphene to 75 parts of dimethylformamide and ultrasonically disperse them uniformly, then add 100 parts of terephthalic acid, 40 The mixture was stirred at 120 rpm for 40 min, then the pressure was reduced to 102 Pa, and the temperature was raised to 265° C. for polycondensation for 105 min to obtain polyester PET chips; the polyester chips were dried at 170° C. for 3 h, extruded at 280° C. by an extruder, and then cold-drummed at 16° C. to obtain cast sheets; a graphene-based film with a thickness of 12 μm was obtained by biaxial stretching; and the remaining steps were the same as those in Example 2.

[0049] Comparative Example 2

[0050] The difference between Comparative Example 2 and Example 2 is that there is no step (3), and step (4) is changed to: add 10 parts of three-dimensional graphene and 12 parts of γ-glycidyloxypropyl trimethoxysilane silane coupling agent to 50 parts of dry dimethylformamide, stir at 60rpm for 30min, react at 35°C for 18h, cool to room temperature and filter, wash twice with dimethylformamide, dry at 50°C to constant weight, and obtain surface-modified graphene; add 25 parts of surface-modified graphene to 75 parts of dimethylformamide and ultrasonically disperse them uniformly, and then add 100 parts of terephthalic acid, 40 parts of ethylene glycol, 1.5 parts of antimony trioxide catalyst and 1.5 parts of triphenyl phosphate stabilizer were stirred at 120 rpm for 40 min, then the pressure was reduced to 102 Pa, and the temperature was raised to 265°C for polycondensation for 105 min, and polyester PET chips were obtained; the polyester chips were dried at 170°C for 3 h, extruded at 280°C by an extruder, and then cold-drummed at 16°C to form a cast sheet; a graphene-based film with a thickness of 12 μm was obtained by biaxial stretching; the remaining steps were the same as in Example 2.

[0051] Comparative Example 3

[0052] The difference between Comparative Example 3 and Example 2 lies in the difference in step (3). Step (3) is changed to: using single crystal SiC as a substrate, spreading the bombarded three-dimensional graphene on the substrate, heating to 500°C, opening the baffle of the metal beam source to deposit metal indium atoms, the heating current is 2.5A, the heating temperature is 985K, and the heating time is 20min to obtain metal indium interspersed with the three-dimensional graphene; the remaining steps are the same as Example 2.

[0053] Comparative Example 4

[0054] The difference between Comparative Example 4 and Example 2 is that there is no step (5), and step (4) is changed to: add 10 parts of metal indium interlaced three-dimensional graphene and 12 parts of γ-glycidyl ether oxypropyl trimethoxysilane silane coupling agent to 50 parts of dry dimethylformamide, stir at 60rpm for 30min, react at 35°C for 18h, cool to room temperature and filter, wash twice with dimethylformamide, and dry at 50°C to constant weight to obtain surface-modified graphene; add 25 parts of surface-modified graphene to 75 parts of dimethylformamide and ultrasonically disperse them uniformly, and then add 100 parts of terephthalic acid, 40 parts of ethylene glycol, 1.5 parts of antimony trioxide as a catalyst and 1.5 parts of triphenyl phosphate as a stabilizer were added, stirred at 120 rpm for 40 min, then the pressure was reduced to 102 Pa, and the temperature was raised to 265° C. for polycondensation for 105 min, and polyester PET chips were obtained; the polyester chips were dried at 170° C. for 3 h, extruded at 280° C. by an extruder, and then cold-drummed at 16° C. to form a cast sheet; a stable graphene-based film with a thickness of 12 μm was obtained by biaxial stretching; the remaining steps were the same as those in Example 2.

[0055] Comparative Example 5

[0056] The difference between Comparative Example 5 and Example 2 lies in step (5). Step (5) is changed to: modifying the film by triboelectric microplasma, using copper film as the positive electrode material and polytetrafluoroethylene as the negative electrode material for the friction nanogenerator, cutting the copper foil and polytetrafluoroethylene into squares of 10 cm × 10 cm respectively, and then pasting them on acrylic plates of the same size as two fixed electrodes, the movement of the friction nanogenerator is controlled by a linear motor, and the high voltage output by the friction nanogenerator acts on the needle tip above the film, controlling the discharge current to be between 5.5 μA, the distance between the needle tip and the film to be 0.5 mm, and the time to be 7 s, thereby obtaining a stable graphene-based film; the remaining steps are the same as Example 2.

[0057] Effect example

[0058] Table 1 below shows the performance analysis results of a single-layer stable graphene-based film and a preparation method thereof using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0059] Table 1

[0060]

[0061]

[0062] From the comparison of the experimental data of the stability of the embodiment and the comparative example, it can be found that the present invention uses a vapor phase chemical deposition method to prepare a single-layer graphene film. As the preparation reaction time increases, the cracked carbon atoms are continuously connected and grown into a film on the surface of the copper foil with the active core as the center, and the single crystal size increases accordingly. The grains are basically oriented parallel to each other to achieve a uniform single-layer structure; and the graphene monomer film formed by the honeycomb-shaped two-dimensional crystal composed of a single layer of hexagonal cell carbon atoms will have a large number of dangling bonds of carbon atoms around it, and other carbon atoms that do not participate in nucleation are connected to it, resulting in the single-layer graphene structure being not stable enough; a three-dimensional porous structure is constructed based on a single-layer graphene, and this multi-dimensional structure effectively increases the specific surface area of ​​the graphene, providing favorable conditions for the subsequent doping of metal particles; nano-scale indium particles are interspersed therein, and the indium particles are bombarded by magnetron sputtering to form particles with sharp angles under impact crushing, thereby combining with the hydroxyl functional groups, carboxyl functional groups, and carbonyl functional groups generated by the dangling bonds of carbon ions, while solving the instability caused by the dangling bonds, the overall conductivity of the film is further improved. The interaction between the prepared graphene and the substrate is weak, and the graphene is in a separated state, which achieves the effect of ionization, is not easy to agglomerate in the subsequent preparation process, and is stably and evenly dispersed in the resin. From the comparison of the experimental data of the conductivity of the embodiment and the comparative example, it can be found that the present invention uses a silane coupling agent as an auxiliary agent to chemically link with the graphene layer, which improves its stability in the resin on the one hand, and makes it difficult to agglomerate and destroy its three-dimensional structure after surface modification on the other hand; the graphene layer is in the resin, and the whole is modified by friction point micro plasma treatment, so that the generated oxygen ions are attached to the surface of the film, which improves the electrical properties of the material and improves its conductivity; at the same time, the state of oxygen ions in the film is not stable, and it can be partially desorbed by heating, thereby realizing the regulation of the stability of the film structure, so that the film can improve the electrical properties while taking into account the stability.

[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A single-layer stable graphene-based film, characterized in that: The film is prepared by vapor-depositing a single-layer graphene to prepare a three-dimensional structure interlaced with metal indium, and then physically modified by combining with a coupling agent.

2. A single-layer stable graphene-based film according to claim 1, characterized in that: The three-dimensional structure is interspersed with metal indium ions by magnetron sputtering bombardment, so that indium particles are crushed by impact to form particles with sharp angles, thereby combining with the three-dimensional graphene carbon ion dangling bonds.

3. A single-layer stable graphene-based film according to claim 1, characterized in that: The physical modification is to perform friction point micro plasma treatment modification on the film, so that the generated oxygen ions are attached to the surface of the film, and then partially desorbed by heating.

4. A method for preparing a single-layer stable graphene-based film, characterized in that: The method comprises the following preparation steps: (1) The copper foil was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water at a power of 30kHz for 10 minutes respectively; the cleaned copper foil was placed in a quartz boat and placed in a stable temperature zone in the furnace tube, and the tube mouth was closed; the vacuum pump was turned on to evacuate the air in the system, and when the vacuum degree reached -0.1MPa, the outlet valve was closed, and H2 was introduced until the system was at normal pressure. At this time, H2 was turned off, and the outlet valve was opened to continue vacuuming, and this was repeated twice; the heating function of the tubular furnace was turned on to anneal the copper foil; after the annealing was completed, the H2 flow rate was maintained, the temperature was adjusted to 1000-1060°C, CH4 was introduced, the flow rate was controlled at 10-50sccm, the reaction time was 10-50min, and CH4 was turned off after the reaction was completed; the heating function of the tubular furnace was turned off, and the temperature was lowered while keeping the H2 flow rate unchanged; after it dropped to room temperature, H2 was turned off, the vent valve was opened until the system was at normal pressure, and the sample was taken out to obtain a single-layer graphene; (2) Prepare 12-16 parts of 5-15% ethyl cellulose ethanol solution, stir at 60 rpm for 20 min, then add 9.8 parts of terpineol and 9.2 parts of anhydrous ethanol; finally add 0.1-0.2 parts of the prepared ground single-layer graphene powder, stir magnetically at 150-250 rpm for 20-30 min, then ultrasonically disperse at 40 kHz for 20 min, alternating 3-5 times; then stir and evaporate at 50° C. and 600-1000 rpm until no more weight loss occurs, then add 0.5-0.7 parts of acetylacetone and 0.6-0.8 parts of OP emulsifier are added, and graphene slurry is obtained after stirring at 100 rpm for 30 minutes; 3-5 layers of graphene slurry are screen-printed on the cleaned FTO glass conductive surface, and pre-treated in a forced air drying oven at 80-120° C. for 20 minutes, and then the printing is repeated, and the surface is cured at 100-150° C. for 2-4 hours, and then 3-5 layers of graphene slurry are printed, and finally the surface is heat-treated at 100-400° C. for 1 hour in a muffle furnace, and then cooled to room temperature to obtain three-dimensional graphene; (3) turning on the hydrogen source in the magnetron sputtering vacuum chamber, and sputtering hydrogen with a radio frequency power of 100-150W to generate hydrogen plasma, and bombarding the three-dimensional graphene with the hydrogen plasma; using single crystal SiC as a substrate, laying the bombarded three-dimensional graphene on the substrate, heating to 450-550°C, opening the baffle of the metal beam source to deposit metal indium atoms; then turning on the nitrogen source in the magnetron sputtering vacuum chamber, sputtering nitrogen with a radio frequency power of 100-150W to generate nitrogen plasma, and bombarding the deposited composite with the nitrogen plasma; then annealing at 500-750°C, maintaining for 15-30min to obtain metal indium interspersed with the three-dimensional graphene; (4) adding 10 parts of metal indium interpenetrating three-dimensional graphene and 10-14 parts of silane coupling agent to 50 parts of dry dimethylformamide, stirring at 60 rpm for 30 minutes, reacting at 20-50° C. for 12-24 hours, cooling to room temperature and filtering, washing with dimethylformamide twice, and drying at 50° C. to constant weight to obtain surface-modified graphene; adding 5-50 parts of surface-modified graphene to 50-100 parts of dimethylformamide and ultrasonically dispersing them uniformly, and then adding 100 parts of terephthalic acid and 35-45 parts of ethylene dichloride; alcohol, 1-2 parts of catalyst and 1-2 parts of stabilizer, stirring at 60-180rpm for 20-60min, then reducing the pressure to 102Pa, and heating to 250-280℃ for polycondensation for 30-180min, and discharging the material to obtain polyester PET chips; drying the polyester chips at 160-180℃ for 2-4h, extruding them at 265-295℃ through an extruder, and then cooling them at 12-20℃ to make casting sheets; and biaxially stretching to obtain a graphene-based film with a thickness of 3-20μm; (5) The film was modified by triboelectric microplasma. The friction nanogenerator used copper film as the positive electrode material and polytetrafluoroethylene as the negative electrode material. The copper foil and polytetrafluoroethylene were cut into squares of 10 cm × 10 cm respectively and then pasted on acrylic plates of the same size as two fixed electrodes. The movement of the friction nanogenerator was controlled by a linear motor. The high voltage output by the friction nanogenerator acted on the needle tip above the film, and the discharge current was controlled to be between 4.5 and 6.5 μA. The distance between the needle tip and the film was 0 to 1 mm, and the time was 0 to 14 s. After being treated at 160 to 200 °C for 5 to 15 min, a stable graphene-based film was obtained.

5. The method for preparing a single-layer stable graphene-based film according to claim 4, characterized in that: The annealing process conditions of step (1) are as follows: temperature of 1050° C., time of 20 min, hydrogen flow rate of 10 sccm, and a vacuum gauge indicating a pressure of approximately -0.1 MPa.

6. The method for preparing a single-layer stable graphene-based film according to claim 4, characterized in that: The single-layer graphene grinding process in step (2) is as follows: the mass ratio of cobalt oxide ball milling beads to single-layer graphene is 2000-10000:1, the rotation speed is 200-400rpm, and the ball milling time is 10-30h.

7. The method for preparing a single-layer stable graphene-based film according to claim 4, characterized in that: The deposition process conditions in step (3) are as follows: a heating current of 2.0-3.0A, a heating temperature of 950-1020K, and a heating time of 15-25min.

8. The method for preparing a single-layer stable graphene-based film according to claim 4, characterized in that: The silane coupling agent in step (4) is one of γ-glycidyloxypropyltrimethoxysilane and silane coupling agent KH550.

9. The method for preparing a single-layer stable graphene-based film according to claim 4, characterized in that: The catalyst in step (4) is antimony trioxide.

10. The method for preparing a single-layer stable graphene-based film according to claim 4, characterized in that: In the step (4), the stabilizer is triphenyl phosphate.

Citation Information

Patent Citations

  • Graphene transparent conductive film and preparation method thereof

    CN105788753A

  • Preparation method of three-dimensional porous graphene thin film built by single-layer graphene

    CN106744841A

  • Method for preparing monolayer monocrystalline square graphene

    CN109957836A

  • Preparation method of graphene oxide metal nanosheet composite material

    CN112376027A

  • Single-layer graphene resistance switch

    CN117377380A